DFA/MOST results - Judt, David M.; Lawson, Craig P.; Lockett, Helen (Cranfield University, 2017)
Results for the empirical analysis of the assembly tasks using DFA and basic MOST
Keywords: Predetermined time measurement process'; 'Design for assembly'; 'MOST'; 'Aircraft system assembly'; 'Aerospace Engineering'